Struktur Komunitas Fitoplankton di Perairan Muara Sungai Bengawan Solo, Ujung Pangkah, Jawa Timur - Syafarina, R.; Widodo, R.; Sulistiono, Sulistiono; Pertiwi, Niken T. M. (Universitas Jambi, 2018)
Estuary is one of an aquatic ecosystem that has something unique, because it is a meeting area of the fresh and sea water. This study aimed to analyze phytoplankton structure community in estuary of Bengawan Solo River, conducted from January to June 2001 at ten stations distributing from river, estuary and sea. Data analysis was done to evaluate species composition, abundance, diversity, evenness, and dominance indices of the phytoplankton. Clustering based on the phytoplankton abundance was done by using Bray Curtis index. Based on the study, the phytoplankton in the estuary of Bengawan Solo River consisted of 5 classes and 33 species such as. Bacillariophyceae (19 species), Cyanophyceae (2 species), Crysophyceae (3 species), Chlorophyceae (3 species) and Dinophyceae (6 species). Phytoplankton abundance varied, at the river station was 1026-3005 inde/l, the estuary was 5098-19727 inde/l, and the sea was 4206-8697 inde/l. Diversity Index (H) was 0, 29-2, 24, Evenness Index (E) was 0, 02-0, 98, and Dominant Index (C) was 0, 12-0, and 88. There were 3 groups according to clustering analysis based on the phytoplankton abundance using Bray Curtis Index (55%).